Outcome and management of antenatal patients with jaundice in tertiary care centre of eastern India: a retrospective study - Singh, Kalpana; Kumar, Gopal; Singh, Anshu; Rani, Anjali (International Journal of Research in Medical Sciences, 2017)
Background: Aim of current study was to know the etiological factors of jaundice among pregnant patients, outcome and their management. Methods: A retrospective study done at IMS, BHU in obstetrics and gynecology department among pregnant patients with jaundice admitted in obstetric wards and labour room in six months duration. Results: Among total 1960 admissions, 78 (3.97%) patients presented with jaundice. Out of all admissions 27 (1.37%) were HBSAg, 8 (0.40%) HEV, 7 (0.35%) HCV, 6 (0.30%) of HBSAg and HEV co-infection, cholestasis with pregnancy 20 (1%) and 10 (0.51%) patients with pre-eclamptic liver disease with HELLP. Conclusions: Jaundice in pregnancy may be lethal to mother and fetus. As the course of disease is also rapid and in short period it may affect the fetus in utero also, early detection and prompt management of these cases should be done.